Elsewhere [videorecording (DVD)] - Geyrhalter, Nikolaus, 1972- (Icarus Films Home Video, 2010)
An epic journey to twelve remote and rarely glimpsed locales and communities around the world. Geyrhalter films expansive vistas of desert, snow, jungle, ice, and rainforest, travels with a scooter-riding Finnish reindeer herdsman, visits the home of a Namibian couple with relational problems, ventures out to sea with a Sardinian fisherman, creating twelve twenty-minute portraits from twelve remote places on five continents.